1, 3-Indanedione functionalized fluorene luminophores: Negative solvatochromism, nanostructure-morphology determined AIE and mechanoresponsive luminescence turn-on. (August 2018) - Zhang, Fang; Zhang, Rong; Liang, Xiaozhong; Guo, Kunpeng; Han, Zhaoxiang; Lu, Xiaoqing; Xie, Jingjuan; Li, Jie; Li, Da; Tian, Xia
Abstract: Luminous efficiency in polar environment and aggregated state, as well as high-contrast luminescence on/off switching under external stimuli are significant issues to be addressed in developing functional fluorescent materials. Combining the advantages of solvatochromic effect in intramolecular charge transfer (ICT) compounds with their nanostructured morphological effects, we herein report a series of A–π–D–π–A fluorene derivatives, which simultaneously exhibit negative solvatochromism, aggregation-induced emission (AIE) and mechanoresponsive luminescence (MRL) turn-on. These molecules contain the same fluorene donor (D) and 1, 3-indandione acceptor (A) but differ in alkyl substituents in the 9-position of the fluorene segment, including 9, 9-dibutyl ( b -DIPF ), 9, 9-dioctyl ( o -DIPF ) and 9, 9-didodecyl ( d -DIPF ). The emission colors of these compounds were changed from blue to orange-red, and the fluorescence quantum yields increased upon increasing the solvent polarity from nonpolar hexane to polar dimethyl sulfoxide. Due to the formed random nanostructured aggregates, the compounds exhibited AIE characteristics in THF/H2 O mixtures. Oppositely, their emission quenched 0D particles which were afforded by quick evaporation of their dichloromethane solvents under vacuum displayed remarkable mechanoresponsive luminescence turn-on behavior. Our results suggest that rationally design ICT molecules and control their nanostructures would be promising way for realizing multifunctional fluorescent materials. Graphical abstract: A series of 1, 3-indanedione functionalized fluorene luminophores simultaneously exhibit negative solvatochromism, AIE and mechanoresponsive luminescence turn-on were realized by taking the advantages of ICT and nanostructured morphological effects. Highlights: Organic luminophores exhibit versatile fluorescent behaviors in different states. The luminophores exhibit negative solvatochromism in solutions. The fluorescent behaviors in aggregates are determined by nanostructure morphologies. The random aggregates of the luminophores exhibit aggregation-induced emission. The 0D particles of the luminophores exhibit mechanoresponsive luminescence turn-on.